2016
DOI: 10.1152/ajpheart.00998.2015
|View full text |Cite
|
Sign up to set email alerts
|

The adipokine chemerin amplifies electrical field-stimulated contraction in the isolated rat superior mesenteric artery

Abstract: Darios ES, Winner BM, Charvat T, Krasinksi A, Punna S, Watts SW. The adipokine chemerin amplifies electrical field-stimulated contraction in the isolated rat superior mesenteric artery. Am J Physiol Heart Circ Physiol 311: H498 -H507, 2016. First published July 1, 2016; doi:10.1152/ajpheart.00998.2015.-The adipokine chemerin causes arterial contraction and is implicated in blood pressure regulation, especially in obese subjects with elevated levels of circulating chemerin. Because chemerin is expressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…These conclusions have been supported by other laboratories that noted the importance of the endothelium in protecting against chemerin-induced contraction (Neves et al, 2014). The normal SMA also has the ability to contract in a chemerin receptor-dependent manner when stimulated with an electrical field, a contraction that was dependent on PVAT and the sympathetic nervous system (Darios et al, 2016). We have identified the mechanism of vascular contraction in normal animals as an operation through the smooth muscle cells themselves that works in a calcium-dependent manner (Ferland et al, 2017).…”
Section: Introductionsupporting
confidence: 57%
“…These conclusions have been supported by other laboratories that noted the importance of the endothelium in protecting against chemerin-induced contraction (Neves et al, 2014). The normal SMA also has the ability to contract in a chemerin receptor-dependent manner when stimulated with an electrical field, a contraction that was dependent on PVAT and the sympathetic nervous system (Darios et al, 2016). We have identified the mechanism of vascular contraction in normal animals as an operation through the smooth muscle cells themselves that works in a calcium-dependent manner (Ferland et al, 2017).…”
Section: Introductionsupporting
confidence: 57%
“…Moreover, these effects are exaggerated in thoracic aorta and mesenteric arteries with reduced endothelium‐dependent relaxation, a phenomenon often found in hypertension and obesity (Watts et al , ). A follow‐up study by the same group (Darios et al , ) has also shown that PVAT‐derived chemerin potentiates sympathetic contraction through its receptor, which is co‐localized with tyrosine hydrolase in sympathetic nerves of rat superior mesenteric artery. Direct application of chemerin to isolated aorta or mesenteric artery also augments agonist‐induced contraction in a manner dependent on endothelin ET A receptors and ERK activation (Lobato et al ., ) and increases systolic blood pressure in mice (Kunimoto et al ., ).…”
Section: Evidence For Contractile Factors From Pvatmentioning
confidence: 90%
“…The expansion of PVAT is also likely to involve the generation of pre‐adipocytes from resident mesenchymal stem cells and maturation of pre‐adipocytes (Pellegrinelli et al ., ). Moreover, PVAT is also innervated by sympathetic nerves (Bulloch and Daly, ; Darios et al , ), which could stimulate the browning of PVAT. However, the interactions among perivascular adipocytes, immune cells and nerves in vascular regulation remain poorly defined.…”
Section: Composition Of Pvatmentioning
confidence: 99%
“…Furthermore, PVAT represents a source of so-called adipocytederived relaxing factor(s) (ADRF), that have potent relaxant or anticontractile properties [31,32] . Apart from these actions being demonstrated in blood vessels from experimental animals [37][38][39] , PVAT has been shown to possess anticontractile actions in isolated preparations of the human internal thoracic artery (ITA) [40] and SV [41] . Although specific ADRFs have not yet been identified, various candidates have been suggested, including NO [42] , leptin [32,43] , H2S [44] , adiponectin [45,46] , and prostaglandins [41,47] .…”
Section: Perivascular Fatmentioning
confidence: 99%